The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.2527/jas.2016-0811
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic analysis of seminal plasma and sperm cells and their associations with semen freezability in Guzerat bulls1

Abstract: The objective of the present study was to describe the relationship of seminal plasma and total sperm cell proteins with the semen freezability parameters of Guzerat bulls. Thirteen bulls were subjected to breeding soundness evaluation. Semen samples were collected, cryopreserved, and then post-thawing sperm kinetics were assessed, where high ( = 7) and low ( = 6) freezability groups were defined. Seminal plasma and total sperm proteins from the 2 groups were separated by 2-dimensional SDS-PAGE, and spots were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
84
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(87 citation statements)
references
References 70 publications
3
84
0
Order By: Relevance
“…Other studies conducted in bull, ram and buck revealed that quantitative variations in seminal plasma and sperm proteins also appeared between males [90][91][92][93][94][95][96], which could explain in part the individual variability observed in sperm freezability [97,98]. Males are frequently categorized as good or bad freezers depending on their post-thaw sperm quality; however, molecular biomarkers could predict more efficiently sperm cryotolerance before freezing-thawing in different individuals [10].…”
Section: Molecular Mechanisms Involved In Those Factors That May Affementioning
confidence: 99%
See 1 more Smart Citation
“…Other studies conducted in bull, ram and buck revealed that quantitative variations in seminal plasma and sperm proteins also appeared between males [90][91][92][93][94][95][96], which could explain in part the individual variability observed in sperm freezability [97,98]. Males are frequently categorized as good or bad freezers depending on their post-thaw sperm quality; however, molecular biomarkers could predict more efficiently sperm cryotolerance before freezing-thawing in different individuals [10].…”
Section: Molecular Mechanisms Involved In Those Factors That May Affementioning
confidence: 99%
“…Among them, proteins involved in energy metabolism, motility regulation and sperm membrane protection increased in abundance in males classified as good freezers (Table 1). These changes could explain the greater sperm viability, mitochondrial activity and motility of good freezers compared to bad freezers [90][91][92][93][94][95][99][100][101]. In this context, freezability biomarkers can be a useful tool to select those males with a superior sperm freezing resilience.…”
Section: Molecular Mechanisms Involved In Those Factors That May Affementioning
confidence: 99%
“…ANXA1 and PAFA were both shown to be significantly higher in bulls with low sperm freezability. However, in the same study, ANXA1 was more pronounced in sperm protein extracts from bull with high freezability (Rego et al, 2016). These studies support that ANXA1 is involved in promotion of membrane aggregation and fusion events and likely involved in membrane repair (Rescher & Gerke, 2004).…”
Section: Discussionmentioning
confidence: 80%
“…The protein is associated with the cell surface and is involved in epithelial cell proliferation, direct cell migration, and angiogenesis (Coulthard et al, 2012). It has been identified to be increased in bulls with low freezability, and speculated to be involved in inflammatory response, with increases occurring in response to oxidative stress (Rego et al, 2016). In the same study Acrosin inhibitor 1 (SPINK6) was shown to be negatively associated with postthaw sperm motility in B. indicus bulls; where a higher acrosin release from the acrosome before cryopreservation, may result in reduced cryotolerance (Rego et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation